Răspuns :
101x[101-(101-102:x)]=202
101-(101-102:x)=202:101
101-(101-102:x)=2
101-102:x=101-2
101-102:x=99
102:x=101-99
102:x=2
2x=102
x=102:2
x=51
369-[(x+112):5+113]=343
(x+112):5+113=369-343
(x+112):5+113=26
(x+112):5=26-113
(x+112):5=-87
x+112=-87·5
x+112=-435
x=-547
101-(101-102:x)=202:101
101-(101-102:x)=2
101-102:x=101-2
101-102:x=99
102:x=101-99
102:x=2
2x=102
x=102:2
x=51
369-[(x+112):5+113]=343
(x+112):5+113=369-343
(x+112):5+113=26
(x+112):5=26-113
(x+112):5=-87
x+112=-87·5
x+112=-435
x=-547
101×[101-(101-102:X)] = 202
[101-(101-102:X)] = 202:101
101-(101-102:X) =2
101-102:X = 101-2
102:X = 101-99
102:X = 2
X = 102:2
X = 51
Verificare:
101×[101-(101-99)] = 101×(101-99) = 101×2 = 202
369-[(X+112):15+113] = 434
(X+112):15+113 = 369-434
(X+112):15+113 = -65
(X+112):15 = -65-113
(X+112):15 = -178
X+112 = -178×15
X+112 = - 2 670
X = -2 670-112
X = -2 782
Verificare:
369-(-2670:15+113) = 369- ( -178+113) =
= 369- (- 65) = 369+65 = 434
[101-(101-102:X)] = 202:101
101-(101-102:X) =2
101-102:X = 101-2
102:X = 101-99
102:X = 2
X = 102:2
X = 51
Verificare:
101×[101-(101-99)] = 101×(101-99) = 101×2 = 202
369-[(X+112):15+113] = 434
(X+112):15+113 = 369-434
(X+112):15+113 = -65
(X+112):15 = -65-113
(X+112):15 = -178
X+112 = -178×15
X+112 = - 2 670
X = -2 670-112
X = -2 782
Verificare:
369-(-2670:15+113) = 369- ( -178+113) =
= 369- (- 65) = 369+65 = 434